Water quality assessment of Tasik Biru Seri Kundang for potable drinking water - Nur Syabila Sidek Ahmad; Norhafezah Kasmuri; Helmy Selim; Satoto Edar Nayono; Amin Mojiri (Penerbit Universiti Kebangsaan Malaysia, 2024)
Malaysia’s water supply has shifted from abundant to scarce, prompting a thorough examination of potential solutions, particularly using Tasik Biru Seri Kundang’s untapped resources. Assessing the reservoir’s capacity to provide clean water consistently amidst increasing demand is crucial. The objective was to analyze Tasik Biru Seri Kundang’s water characteristics to determine its suitability as a drinking water source, which was evaluated through the Water Quality Index (WQI) and heavy metal concentration measurements. The water quality analysis involved field and laboratory testing, assessing parameters such as pH, dissolved oxygen, turbidity, chemical oxygen demand (COD), biochemical oxygen demand (BOD), suspended solids (SS), and ammonia-nitrogen (AN). The findings of the study showed that the pH was 7.26 and 7.67, the dissolved oxygen (DO) was 9.77 and 7.15 mg/L, the chemical oxygen demand (COD) and biochemical oxygen demand (BOD) was 0 mg/L each, the suspended solids (SS) were 10 and 7 mg/L. The ammonia-nitrogen (AN) was 0.08 and 0.1 mg/L, separately. According to the results, all input points were categorized as Class I, indicating that no treatment was required for the water supply. Concentrations of heavy metals, including chromium (Cr), iron (Fe), copper (Cu), zinc (Zn), and manganese (Mn), were measured at levels such as 0.017 and 0.086 mg/L for chromium (Cr), 0.25 and 0.53 mg/L for iron (Fe), 0.21 and 0.26 mg/L for zinc (Zn), 0.09 and 0.08 mg/L for copper (Cu), and 0.021 and 0.044 mg/L for manganese (Mn). While most parameters met WHO standards, chromium levels at the outlet exceeded the permissible limit of 0.05 mg/L, indicating a high concentration of heavy metals. Tasik Biru Seri Kundang exhibits favourable water quality characteristics, primarily meeting drinking water standards. However, elevated chromium levels at the outlet point necessitate corrective measures to ensure compliance with regulatory guidelines and safeguard public health.